The Theme of Love in Sarojini Naidu’s Poetry - Chouhan, Sandhya (International Journal of Advanced Research in Peace, Harmony and Education; Vol 4 (2019): International Journal of Advance Research in Peace, Harmony and Education, 2019)
Love is the dominant theme of Sarojini Naidu’s poetry. There are a large number of love-lyrics in the store of her poetry. As a love-lyricist, Sarojini Naodu is superb. Her lyrics deal with human love to metaphysical love. Thus, her love-lyrics have an aesthetic approbation of contemplation and sensation. How to cite this article:  Chouhan S. The Theme of Love in Sarojini Naidu’s Poetry. Int J Adv Res Peace Harm Edu 2019; 4: 10-12. DOI: https://doi.org/10.24321/2455.9326.201903